2021
DOI: 10.1002/joc.7044
|View full text |Cite
|
Sign up to set email alerts
|

Metrological evaluation of the effect of the presence of a road on near‐surface air temperatures

Abstract: With the purpose of revising World Meteorological Organization's Commission for Instruments and Methods of Observation (WMO/CIMO) Guide #8 on weather stations siting, an experiment to evaluate metrologically the maximum influence of a paved road on 2-m air temperature measurements ("road siting effect") has been designed, installed and run in Italy. It consists of a 100-m long array of seven measurement stations, at increasing distances from a local road, equipped with shielded Pt100 thermometers and ancillary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…In any case, this would go beyond the scope of the work, given that it focused on relative differences caused by reflected radiation only, and that there is much more literature dealing with the effect of incident radiation. Erell et al (2005), for instance, showed that no shield provides complete protection from incident radiation, with relative uncertainties up to 1.5 • C. Lopardo et al (2014), showed that an aged, darkened screen can introduce uncertainties up to a similar values, especially at daily maxima.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In any case, this would go beyond the scope of the work, given that it focused on relative differences caused by reflected radiation only, and that there is much more literature dealing with the effect of incident radiation. Erell et al (2005), for instance, showed that no shield provides complete protection from incident radiation, with relative uncertainties up to 1.5 • C. Lopardo et al (2014), showed that an aged, darkened screen can introduce uncertainties up to a similar values, especially at daily maxima.…”
Section: Discussionmentioning
confidence: 99%
“…Only a 3 m wide local road with almost no traffic and a small unoccupied building were present in the area at a distance of more than 50 m from the measuring point. Coppa et al (2021b) performed a metrological quantification of the influences on air temperature measurements introduced by the proximity of roads that revealed a significant effect only at closer distances (less than 50 m) and mainly at very low or even null values of incident radiation; the presence of this infrastructure was therefore considered negligible. According to a similar experiment for the evaluation of the effect of buildings (Garcia Izquierdo et al, 2021), a building of the size of the hut and at that distance causes no influence in air temperature records.…”
Section: Measurement Site and Experimental Set-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Only a 3-m wide local road with almost no traffic and a small unmanned building were present in the area, at more than 50 m from the measuring point. Coppa et al, (2021) performed a metrological quantification of the influences on air temperature measurements introduced by the proximity of roads, that revealed a significant effect only at closer distances (less than 50 m) and mainly at very low or even null values of incident radiation. Since for this experiment only records associated to sun radiation are relevant and the road is at more than 50 m, its presence was considered negligible.…”
Section: Measurement Site and Experiments Set-upmentioning
confidence: 99%
“…Therefore, a thermometer screen with various structures is designed and used to observe air temperature (van der Meulen & Brandsma, 2008). However, the thermometer screens of various designs have different structures, therefore, they have their thermal characteristics (Coppa et al, 2021). While observing the temperature, the inherent thermal characteristics of the thermometer screen get influenced, causing differences between the structures of the thermometer screen even in the same weather station (WS) (Aoshima et al, 2010).…”
Section: Introductionmentioning
confidence: 99%